Efficiency Comparison of Various Parking Charge Schemes Considering Daily Travel Cost in a Linear City - Zhang, Xiaoning; Wee, Bert van (European Journal of Transport and Infrastructure Research, 2011)
In this paper, we introduce a new duration dependent parking fee regime based on the travel cost for an entire day, rather than a single commute trip. Commuters are assumed to reside at one end of a linear city and work in a business center at the other end. A two-stage differential method is used to derive user equilibrium travel patterns for both morning and evening rush hour commutes. Both individual travel cost and system travel cost are derived as functions of travel demand. We then compare the efficiency of the duration dependent parking fee regime with that of three previously proposed pricing regimes in the context of elastic travel demand. Results show that a pricing regime with both time-varying road tolls and location dependent parking fees is most efficient, followed by a regime with time-varying road tolls alone. Depending on the parking fee rate, a uniform duration-based parking fee regime may or may not be more efficient than a no-pricing regime. Under the duration dependent parking fee regime, an optimal parking fee rate can be obtained by minimizing system cost or maximizing social surplus, which gives rise to a system-wide performance no worse than that in the no-pricing regime.